NONLINEAR INTERACTION GETEROSTRUCTURE WITH LASER RADIATION - Kurenkeev, Т.B.; Kurenkey, B.Т. (Recent Contributions to Physics, 2018)
The interaction of a periodic dielectric medium with laser radiation. The effective dielectric permittivity of heterostructures with linear and nonlinear interactions.